Emotional stimulation processing characteristics in depression: Meta-analysis of eye tracking findings - Huang, Genying; Li, Yafang; Zhu, Huizhong; Feng, Hong; Shen, Xunbing; Chen, Zhencai (Frontiers in Psychology, 2023)
Objective: To systematically evaluate the attentional bias in patients with depression toward emotional stimuli and to explore eye movement indicators and potential regulatory variables that can distinguish such patients from healthy individuals. Methods: Case–control studies regarding eye movement-tracking in major depressive disorder published in PubMed, Web of Science, ScienceDirect, The Cochrane Library, EBSCOhost, China National Knowledge Infrastructure, Wanfang, and VIP databases from database initiation until March 12, 2022 were included in the present meta-analysis. Two researchers independently screened the literature and performed data extraction. The quality of the literature was assessed using the Newcastle–Ottawa quality assessment scale. Results: Overall, 14 studies were included, including 1,167 participants (Ndepression = 474; Nhealthy = 693). We found that (1) fixation duration was significantly lower for positive emotional stimuli in the depression group than that in the healthy group; however, for negative stimuli, the fixation duration was significantly more in the depression group than in the healthy group. No significant difference was observed in terms of neutral emotional stimuli between groups. (2) Patients with depression exhibited a significantly lower fixation count for positive emotional stimuli than healthy individuals , whereas the fixation count for negative emotional stimuli was significantly higher in the depression group than in the healthy group . No significant difference was found for neutral emotional stimuli between groups . (3) No significant difference was detected in terms of the first fixation duration of the positive, negative, and neutral emotional stimuli between groups . (4) Moderator analysis indicated that age moderated fixation duration for positive emotional stimuli. In addition, age and the type of negative emotional picture moderated fixation duration for negative emotional stimuli. Conclusion: Patients with depression exhibit a negative attention bias toward emotional stimuli, and the fixation duration and number of gaze times can be used as indicators to distinguish such patients from healthy individuals.